Nephrotoxicity of gentamicin and ceftriaxone combination in male rats - (:unkn) unknown (My University, 2002)
The nephrotoxicity of gentamicin is well known. However, little information is available regarding the combined effects of gentamicin plus ceftriaxone which is used to treat various Gram negative infections. Therefore, male Wistar rats were treated daily with 100 mg/kg gentamicin or 100 mg/kg gentamicin plus 800 mg/kg ceftriaxone for 14 days i.p. Serum biochemical parameters were measured on days 0, 8 and 15. Histopathological examination of kidneys was performed on day 15, one day following the end of treatment. Gentamicin treated rats exhibited an 83% increase in blood urea nitrogen (BUN), a 137% increase in uric acid, and a 63% decrease in serum potassium levels on day 15. The combination of gentamicin plus ceftriaxone partially ameliorated these effects, particularly the increase in uric acid. No significant change in creatinine was observed with the combination treatment. Compared to the control animals, the combination of gentamicin plus ceftriaxone resulted in a 41% and 81% increase in BUN on days 8 and 15, respectively. Histopathological examination of the kidneys suggested a lower degree of nephrotoxicity in rats treated with gentamicin plus ceftriaxone compared to animals treated with gentamicin alone. The results support the importance of monitoring serum biochemical parameters when treating with gentamicin or gentamicin plus ceftriaxone.
Keywords: Blood urea nitrogen; Ceftriaxone; Combination therapy; Creatinine; Gentamicin; Gram negative infections; Kidney function; Nephrotoxicity